2018
DOI: 10.1536/ihj.16-607
|View full text |Cite
|
Sign up to set email alerts
|

Pravastatin Decreases Infarct Size Induced by Coronary Artery Ischemia/Reperfusion with Elevated eNOS Expression in Rats

Abstract: Our previous study showed that pravastatin prevents ischemia and reperfusion-induced lethal ventricular fibrillation in rats. This study explored whether pravastatin decreases myocardial infarct size and this effect is associated with endothelial nitric oxide synthase (eNOS) expression in myocardium. Rats were treated with ischemia (30 minutes) and reperfusion (60 minutes) after chronic oral administration of pravastatin, fluvastatin, or vehicle once daily for 22 days. Electrocardiograms and blood pressure wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 45 publications
1
6
0
1
Order By: Relevance
“…Previous studies have shown that pravastatin can effectively prevent fatal ventricular fibrillation caused by ischemia reperfusion and reduce the mortality rate of cardiovascular diseases. 10,11 The report showed that pravastatin pretreatment can play a protective role in fatal ventricular arrhythmia caused by reperfusion by inhibiting [Ca 2+] (i) overload and preventing δ Ψ (M) loss caused by H 2 O 2. 11 Moreover, pravastatin may reduce the death rate of cardiovascular diseases by affecting eNOS expression, and is superior to fluvastatin in reducing infarct size.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous studies have shown that pravastatin can effectively prevent fatal ventricular fibrillation caused by ischemia reperfusion and reduce the mortality rate of cardiovascular diseases. 10,11 The report showed that pravastatin pretreatment can play a protective role in fatal ventricular arrhythmia caused by reperfusion by inhibiting [Ca 2+] (i) overload and preventing δ Ψ (M) loss caused by H 2 O 2. 11 Moreover, pravastatin may reduce the death rate of cardiovascular diseases by affecting eNOS expression, and is superior to fluvastatin in reducing infarct size.…”
Section: Introductionmentioning
confidence: 99%
“…11 Moreover, pravastatin may reduce the death rate of cardiovascular diseases by affecting eNOS expression, and is superior to fluvastatin in reducing infarct size. 10 Related studies have suggested that cardiac damage caused by myocardial ischemia is related to the imbalance of various signal pathways, especially the imbalance of intracellular signal pathways. 12 miRNA, as a small noncoding RNA, can participate in gene regulation and cell activities, such as development, metabolism, proliferation and differentiation.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…After testing, rats were intracardially perfused with 300 mL PBS, then hearts were excised and stained with 2, 3, 5triphenyltetrazolium (TTC) to delineate the detection sites in the outside surface of both the atrium and the ventricle. 24,25) Hearts were post-fixed in paraformaldehyde overnight and dehydrated in a 30% sucrose solution. Then, hearts were sectioned (40 μm), images were taken using a Leica microscope, and the detection sites were visualized by light microscopy (AHBT3; Olympus, Tokyo, Japan).…”
Section: Electrocardiogram Recording and Bp Measurementsmentioning
confidence: 99%